THE ROLE OF HEALTH INFORMATION SYSTEMS IN TRANSFORMING AND ENHANCING THE EFFICIENCY OF ANGOLA’S HEALTH SYSTEM: CHALLENGES AND OPPORTUNITIES - da Caridade Felix Chitanga, Francisca (Srpski medicinski časopis Lekarske komore, 2025)
Health Information Systems (HIS) are systems designed to collect, store, process, and provide information on both individual and population health, as well as on the management, organization, structure, and functioning of the health system. Their primary purpose is to support decision-making aimed at achieving national health goals. The research objectives were to describe the effectiveness of the Health Information System of Angola (HIS Angola), and to identify challenges for implementing and using HIS by users. The research was based on the assumption that the current form of the HIS provides only a minimal set of data necessary for formulating proposals for actions, policies, and practices aimed at improving the quality, financing, and management of health services, as well as reducing inequalities in access to health care. The research employed a bibliographic method and documentary analysis, combining a review of relevant literature on the role of the HIS in Angola and recommended strategies for its transformation and effectiveness, with a comparative analysis of health system indicators. The historical-logical method was used to explore the origin, development, and evolution of the HIS, while the deductive-inductive method was applied to examine the hypothesis regarding the effectiveness of Angola’s HIS. For the descriptive qualitative and quantitative analysis, we will use standard WHO indicators related to health information systems. These include indicators on health policy (e.g., strategic plans and implementation of HIS), health service delivery (e.g., access and utilization), and health system performance (e.g., response time and service quality). Additionally, we will consider indicators reflecting educational (e.g., IT training for health professionals) and financial (e.g., investments in health care and health information and communication technologies) aspects.  The results indicate that Angola's Health Information System (HIS) has improved through the transition to the DHIS2 platform, leading to enhanced data availability and better management of health services. However, significant challenges persist, including limited resources, inadequate infrastructure, uneven distribution of health personnel, and insufficient IT training. Indicators related to health service access and utilization, response time, and service quality suggest only modest progress, while financial investments remain inadequate to support further development of the system.Conclusion: Angola’s HIS has the potential to significantly enhance health system management and service quality. However, to achieve greater effectiveness and improve health coverage and efficiency, sustained investment is needed in human resources, infrastructure, and training, along with a more equitable distribution of health professionals.
Keywords: information system; health indicators; health management; public health